2015
DOI: 10.1021/acs.macromol.5b01176
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Macromonomer Quality in the Ring-Opening Metathesis Polymerization of Macromonomers

Abstract: Various macromonomers (MMs) were synthesized using controlled radical polymerization (CRP) by either directly growing from a norbornene-functionalized initiator or chain transfer agent ("direct-growth" or DG method) or coupling a norbornenyl group to preformed polymers ("growth-then-coupling" or GC method). The degree of control for the ring-opening metathesis polymerization (ROMP) of these MMs was found to be dependent on which synthetic method was used for the MMs. Narrowly dispersed brush polymers were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 45 publications
1
94
0
Order By: Relevance
“…2 Ring-opening metathesis polymerization (ROMP) of norbornene-based macromonomers (MMs) is a powerful strategy for the synthesis of complex functional bottlebrush polymers with diverse functions and applications. 1b,c,3 Multiple functionalities can be installed into such polymers via copolymerization of different MMs, the combination of MMs with small molecule monomers, or by the use of branched MMs that carry several functional species within a single MM; the latter allows for the syntheses of highly uniform multivalent branched bottlebrush polymers (BBPs). 4 For example, we have established a first-generation branched norbornene MM precursor ( G1 , Scheme 1A) that contains two orthogonal functional sites: an alkyne for copper-catalyzed alkyne azide cycloaddition (CuAAC) and a carboxylic acid for carbodiimide coupling, which enables the synthesis of bivalent MMs with two functional domains (e.g., polymers, drug molecules, imaging agents, and ligands).…”
mentioning
confidence: 99%
“…2 Ring-opening metathesis polymerization (ROMP) of norbornene-based macromonomers (MMs) is a powerful strategy for the synthesis of complex functional bottlebrush polymers with diverse functions and applications. 1b,c,3 Multiple functionalities can be installed into such polymers via copolymerization of different MMs, the combination of MMs with small molecule monomers, or by the use of branched MMs that carry several functional species within a single MM; the latter allows for the syntheses of highly uniform multivalent branched bottlebrush polymers (BBPs). 4 For example, we have established a first-generation branched norbornene MM precursor ( G1 , Scheme 1A) that contains two orthogonal functional sites: an alkyne for copper-catalyzed alkyne azide cycloaddition (CuAAC) and a carboxylic acid for carbodiimide coupling, which enables the synthesis of bivalent MMs with two functional domains (e.g., polymers, drug molecules, imaging agents, and ligands).…”
mentioning
confidence: 99%
“…For example, Vermonden and coworkers reported a rapid, non‐S N 2 azidation reaction catalyzed by the ATRP copper catalyst that required only a small excess of NaN 3 and enabled the polymerization, functionalization and subsequent “click” conjugation to be performed in one pot . A variety of approaches, including the use of “click” chemistry, have also been reported for the preparation of macromonomers from ATRP polymers . In particular, the chain‐end substitution of the terminal bromide of ATRP polymers with acrylic acid or methacrylic acid in the presence of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Especially for the vinyl polymers, reversible‐deactivation radical polymerization (RDRP), generally either atom transfer radical polymerization (ATRP) or reversible addition‐fragmentation chain transfer polymerization, is a popular choice owing to its versatility and controllability . However, some studies reported a multimodal MWD or low conversion to the products due to various impurities in MMs prepared via RDRP . Also, G3 is highly active and thus prone to react with impurities as well, resulting in catalyst poisoning, which makes it difficult to precisely control the ROMP reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been well realized that the purity of MMs is very important to achieve the desired conversion (or MW) with well‐defined structures of BBPs. In fact, the MMs for vinyl polymers have been designed via two approaches; direct growing from norbornene derivatives as an initiator or a chain‐transfer agent (direct‐growth [DG] method) or coupling a norbornenyl group to end‐functionalized prepolymers (growth‐then‐coupling [GC] method) . While the RDRP‐based DG method seems straightforward, Xia et al reported that ROMP of DG‐MMs often results in a broad bimodal MWD, which was attributed to the formation of a small trace of α,ω‐dinorbornenyl telechelic polymer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation